2015
DOI: 10.3389/fpls.2014.00756
|View full text |Cite
|
Sign up to set email alerts
|

Ecopiling: a combined phytoremediation and passive biopiling system for remediating hydrocarbon impacted soils at field scale

Abstract: Biopiling is an ex situ bioremediation technology that has been extensively used for remediating a wide range of petrochemical contaminants in soils. Biopiling involves the assembling of contaminated soils into piles and stimulating the biodegrading activity of microbial populations by creating near optimum growth conditions. Phytoremediation is another very successful bioremediation technique and involves the use of plants and their associated microbiomes to degrade, sequester or bio-accumulate pollutants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Contaminated soil was amended with nutrients, inoculated with hydrocarbon degrading bacteria and then used to construct passive biopiles (Germaine et al 2014). Finally, perennial rye grass (Lolium multiflorum) and white clover (Trifolium repens) were sown on the soil surface to complete the ecopile.…”
Section: Phytoremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…Contaminated soil was amended with nutrients, inoculated with hydrocarbon degrading bacteria and then used to construct passive biopiles (Germaine et al 2014). Finally, perennial rye grass (Lolium multiflorum) and white clover (Trifolium repens) were sown on the soil surface to complete the ecopile.…”
Section: Phytoremediationmentioning
confidence: 99%
“…Germaine et al (2014) investigated the effectiveness of a combined phytoremediationÁ biopiling system, termed ecopiling, to remediate petroleum hydrocarbon contaminated soils (1613 mg/kg…”
Section: Phytoremediationmentioning
confidence: 99%
“…According to the EPA (US Environmental Protection Agency) the very hazardous chemicals like benzene, toluene, ethylbenzene, xylenes, and naphthalene are included in the petroleum hydrocarbons (Lehmann et al, 2006, Bojes and Pope 2007, Gao and Collins, 2009, Cook et al, 2010, Boonsaner et al, 2011, Fester et al, 2014, Germaine et al, 2015. These pollutants can affect soil physical characteristics like soil texture and structural status, compaction, saturated hydraulic conductivity, and penetration resistance (Hreniuc et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, a constructed functional microbiome of PAH degrading bacteria (previously isolated from the same site) were encapsulated in calcium alginate beads. It has been previously shown that this is a useful way of inoculating polychlorinated biphenyl and diesel degrading microbes into soil [14,16]. These beads degrade slowly over time, giving the inoculum time to adapt to the conditions of the soil and protecting them from predation and competition.…”
Section: Discussionmentioning
confidence: 99%
“…Germaine et al [14] reported the successful remediation of 4800 m 3 of soil containing low levels (<2000 ppm) of petrochemicals through Ecopiling over a 2 year period. The Ecopile process involves biostimulation of indigenous hydrocarbon degraders, bio-augmentation through inoculation with known PAH degrading consortia and phytoremediation, through the effect of root growth and penetration throughout the soil and the resulting stimulation of microbial activity in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%